Possíveis mecanismos envolvidos na ausência do fenômeno de “one trial tolerance” na linhagem de ratos espontaneamente hipertensos – SHR - Lopez, Giorgia Batlle [UNIFESP] (2006)
The phenomenon of “one-trial tolerance” (OTT) refers to the absence of the anxiolytic effect of benzodiazepines following a previous exposure to the elevated plus maze (EPM). In addition to several behavioral differences in relation to normotensive strains, spontaneously hypertensive rats (SHR) do not present the OTT phenomenon. The aim of the present study was to investigate the mechanisms involved in the absence of the OTT phenomenon in SHR. Experiment 1 was designed to characterize the absence of OTT in SHR, under our experimental conditions. Thus, we verified the effects of chlordiazepoxide, a classic anxiolytic agent, on the behavior of Wistar normotensive rats (Wistar) and SHR, exposed for the first or second time to the EPM. Supporting previous data, our results demonstrated a decrease in the basal level of anxiety presented by SHR. As previously observed, we also verified that, in opposition to Wistar rats, the SHR did not present the phenomenon of OTT. In a first series of experiments, we tried to verify if the absence of OTT presented by SHR would be related to possible memory deficits in this strain. Procedures designed to improve learning/memory (a decrease in the interval between the first and second exposure to the EPM or an increase in the duration of the first exposure) were not able to modify the absence of OTT in SHR. In these experiments, we also verified that both strains presented a decrease in the exploration of the open arms of the EPM throughout the fifteen-minute exposure, demonstrating that there was no learning impairment to the open arm avoidance in SHR. Nevertheless, we observed that after an initial decrease in the time spent in the open arms, there is an increase in the motivation to explore the EPM presented only by SHR in the first and second fifteen-minute exposure. Finally, this increase in the exploration of the open arms throughout the second exposure presented by SHR was potentiated by the administration of chlordiazepoxide (whereas the exploration presented by Wistar rats was not altered). In a second series of experiments, we investigated the possible role of anxiety levels in the first exposure in the absence of the phenomenon of OTT in SHR. Fourty-five-day-old rats (which present an increase in the basal level of anxiety when compared to adult animals) and the administration of an anxiogenic drug (pentylenetetrazole) was used to evaluate the effects of chlordiazepoxide on SHR and Wistar rats in a second exposure to the EPM. Both the 45-day-old SHR and the adult SHR treated with pentylenetetrazole presented increased anxiety levels when compared to control adult SHR in the first exposure. Notwithstanding, these procedures (which were able to increase the levels of anxiety of Wistar and SHR strains) did not prevent the absence of the phenomenon of OTT in the SHR nor the presence of this phenomenon in Wistar rats. Taken as a whole, these data confirm the absence of the OTT phenomenon in SHR and suggest that this absence is not related to a possible impairment of open arm avoidance nor to the decreased basal levels of anxiety presented by this strain. Furthermore, the fact that, on the contrary of Wistar rats, SHR presented a return in their motivation to explore the open arms when exposed for a longer period to the EPM allows the suggestion that this strain becomes “bored” faster when submitted to prolonged exposures to the enclosed arms of the EPM. While this suggestion seems to support the solid literature that suggests this strain as a model of attention-deficit/hyperactivity disorder (ADHD), the return of the motivation to explore the open arms could reintroduce the inherent conflict to explore this naturally aversive area. Such conflict, sensitive to the action of the benzodiazepines, could explain the efficacy of this agent in animals previously exposed to the EPM and, thus the absence of the OTT phenomenon.